2015
DOI: 10.2147/ndt.s78226
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective strategies against calpain-mediated neurodegeneration

Abstract: Calpains are calcium-dependent proteolytic enzymes that have deleterious effects on neurons upon their pathological over-activation. According to the results of numerous studies to date, there is no doubt that abnormal calpain activation triggers activation and progression of apoptotic processes in neurodegeneration, leading to neuronal death. Thus, it is very crucial to unravel all the aspects of calpain-mediated neurodegeneration in order to protect neurons through eliminating or at least minimizing its leth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 115 publications
(146 reference statements)
2
32
0
Order By: Relevance
“…Under physiological conditions, calpain 1 and 2 are involved in neural development, degeneration and synaptic plasticity. However, calcium overloading induces the activation of calpain 1 and 2, which has a deleterious effect on the brain (14,24). Previous studies have revealed that glutamate neurotoxicity is observed in EBI following experimental SAH (11,(25)(26)(27)(28), and that it causes an increase in the intracellular calcium concentration, predominantly through the N-methyl-D-aspartate receptor and the metabotropic glutamate receptor 1 (28), resulting in calpain activation.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, calpain 1 and 2 are involved in neural development, degeneration and synaptic plasticity. However, calcium overloading induces the activation of calpain 1 and 2, which has a deleterious effect on the brain (14,24). Previous studies have revealed that glutamate neurotoxicity is observed in EBI following experimental SAH (11,(25)(26)(27)(28), and that it causes an increase in the intracellular calcium concentration, predominantly through the N-methyl-D-aspartate receptor and the metabotropic glutamate receptor 1 (28), resulting in calpain activation.…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegeneration is the progressive dysfunction and loss of neuronal structure and function that resulted in neuronal cell death [1,2]. Neurodegeneration occurs in various diseases affecting the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…While they remain inactivated in the absence of Ca 2+ , elevation of intracellular calcium levels results in calpain overactivation and, thus, detrimental effects on neurons: abnormally high activity promotes apoptotic processes, neurodegeneration, and, ultimately, neuronal death [42]. In vitro studies indicate that astaxanthin protects porcine lens proteins from hydrolysis by calpains; the results suggest that this carotenoid reacts with calcium ions, decreases the free Ca 2+ level, and thus mitigates the probability of calpain activation [34,43].…”
Section: Astaxanthinmentioning
confidence: 99%